L-cysteine-functionalized CuPt: A chiral electrode for the asymmetric electroreduction of aromatic ketones. (10th April 2021) - Yue, Ying-Na; Wang, Zhuo-Lin; Yang, Li-Rong; Zhao, Yi-Jun; Wang, Huan; Lu, Jia-Xing
Abstract: The heterogeneous chiral catalyst L-cysteine-CuPt prepared by the bonding between the natural and inexpensive L-cysteine and CuPt obtained by a simple method in a green process exceled in this work. L-cysteine showed strong chemisorption through the bonding of the sulfhydryl group with the CuPt, so it could be firmly present on the surface of the alloy. Detailed surface analysis were carried out on the as-prepared L-cysteine-CuPt which was further applied to catalyze the asymmetric electroreduction of aromatic ketones. ( R )-α-(trifluoromethyl) benzyl alcohol with 73% yield and 43% ee was obtained on the L-cysteine-CuPt cathode under the optimized electrolytic reaction conditions. In addition to owning the activity capable of efficiently catalyzing the substrate to produce optically active products, the L-cysteine-CuPt also exhibited strong stability such that the catalytic results did not significantly change on it after repeated use. Graphical abstract: L-cysteine-CuPt is performed as a chiral modified electrode to catalyze the asymmetric electroreduction of pro-chiral aromatic ketones (2, 2, 2-trifluoroacetophenone is selected as a model substrate). Image, graphical abstract